How to cheat in motion simulation - comparing the engineering and fun ride approach to motion cueing - Heyde, M. von der; Riecke, B. E. (Max Planck Institute for Biological Cybernetics, Tübingen, Germany, 2001)
The goal of this working paper is to discuss different motion cueing approaches. They stem either from the engineering field of building flight and driving simulators, or from the modern Virtual Reality fun rides presented in amusement parks all over the world. The principles of motion simulation are summarized together with the technical implementations of vestibular stimulation with limited degrees of freedom. A psychophysical experiment in Virtual Reality is proposed to compare different motion simulation approaches and quantify the results using high-level psychophysical methods as well as traditional evaluation methods. ACKNOWLEDGEMENTS: This research was funded by the Max-Planck Society and the Deutsche Forschungsgemeinschaft (SFB 550 Erkennen, Lokalisieren, Handeln: neurokognitive Mechanismen und ihre Flexibilität).
Keywords: MPI-TR; Riecke; Riecke_2001; TR; bernhard-riecke; iSpaceWeb; markus-von-der-heyde; spatial updating